Sporting pathways to integration: A comprehensive study on the integration of Ukrainian teenage war refugees through sports initiatives - Martin Kölbel (Bern Open Publishing, 2024)
The ongoing crisis in Ukraine has resulted in a significant influx of war refugees seeking safety and stability in various parts of the world especially in European countries. Despite frequent discussions about whether and to what extent displaced people can be integrated correctly into a target country's educational institutions, prevalent pedagogical expertise and scientific inquiry is lacking full-scale comprehension of this complex matter. On a European level, The European Commission in the White paper on sport (2007, p. 7) emphasizes that sport "makes an important contribution to economic and social cohesion and more integrated societies". Consequently, the social impact of sports is accompanied by high political expectations. However, critics might argue that this interpretation is too simplistic as sport cannot solve major societal problems as for example poverty or physical and mental well-being (Coakley, 2011; Spaaij, 2012). Nevertheless, recent research demonstrates that sport is of relevance for fostering societal participation and active citizenship; similarly, it is assumed that sports can increase the typically sparse contact between migrant and non-migrant youth and other social networks (Green, 2007; Lagergren & Fundberg, 2009). Hence this paper analyzes which sporting initiatives both within and outside educational settings help Ukrainian war refugees to get in contact with native or non-migrant social settings in three different receiving host countries (i.e. Austria, Germany and England). Through content analysis of interviews with refugees (N = 10), the study explores the perceived impact of sports activities on various aspects of integration, including social cohesion, sense of belonging, cultural adaptation as well as perceived integration challenges. While interviews with Ukrainian refugees residing in Austria were face-to-face interviews (Cassell & Symon, 2004), interviews with Ukrainian refugees residing in England or Germany were conducted online. All interviews were conducted in English, as the level of English of all interviewees was considered good enough to express their opinions and thoughts. On the basis of a comprehensive analysis of all interviews, four main themes (i.e. curricular sports initiatives, extra-curricular sports initiatives, other initiatives, integration challenges) emerged. Results highlight the importance of the context in which sport initiatives are implemented. While both initiatives within educational institutions and those outside formal education settings were reported to have a positive impact, nuances were observed in their effects on integration. For instance, sports programs within educational institutions were perceived as providing opportunities for structured engagement and skill development, which in turn enhanced participants' sense of inclusion and self-esteem. On the other hand, initiatives outside educational institutions, such as community sports clubs and recreational activities, were valued for their role in fostering informal social networks and facilitating interaction with members of the host community. Overall, it is worth mentioning that while sports initiatives emerged as a valuable resource for promoting integration, they alone cannot address the complex challenges faced by refugees in the process of adapting and integrating into a new social environment. Therefore, a holistic approach that combines sports with other forms of support, such as language training, employment assistance, and psychosocial support, is essential for facilitating successful integration outcomes. References Cassell, C., & Symon, G. (2004). Essential guide to qualitative methods in organizational reserach. Sage. Coakley, J. (2011). Youth sports what counts as "positive development?". Journal of Sport and Social Issues, 35(3), 306-324. https://doi.org/10.1177/0193723511417311 European Commission: Directorate-General for Education, Youth, Sport and Culture (2007). White paper. White paper on sport. Brussels. https://op.europa.eu/en/publication-detail/-/publication/8614cc62-c23e-4b11-8c0b-4c24a71f863d Green, M. (2007). Governing under advanced liberalism: Sport policy and the social investment state.  Policy Sciences, 40(1), 55-71. https://doi.org/10.1007/s11077-007-9034-y Lagergren, L., & Fundberg, J. (2009). Integration i forening - Kritiska reflektioner kring ett projekt [Integration in association - Critical reflections on a project]. Educare, 1, 43-59. https://doi.org/10.24834/educare.2009.1.1287 Spaaij, R. (2012). Beyond the playing field: Experiences of sport, social capital, and integration among Somalis in Australia. Ethnic and Racial Studies, 35(9), 1519-1538. https://doi.org/10.1080/01419870.2011.592205